Dopamine Modulates Serotonin Innervation in the Drosophila Brain - Niens, Janna; Reh, Fabienne; Çoban, Büşra; Cichewicz, Karol; Eckardt, Julia; Liu, Yi-Ting; Hirsh, Jay; Riemensperger, Thomas D. (Frontiers in Systems Neuroscience, 2017)
Parkinson's disease (PD) results from a progressive degeneration of the dopaminergic nigrostriatal system leading to a decline in movement control, with resting tremor, rigidity and postural instability. Several aspects of PD can be modeled in the fruit fly, Drosophila melanogaster, including α-synuclein-induced degeneration of dopaminergic neurons, or dopamine (DA) loss by genetic elimination of neural DA synthesis. Defective behaviors in this latter model can be ameliorated by feeding the DA precursor L-DOPA, analogous to the treatment paradigm for PD. Secondary complication from L-DOPA treatment in PD patients are associated with ectopic synthesis of DA in serotonin (5-HT)-releasing neurons, leading to DA/5-HT imbalance. Here we examined the neuro-anatomical adaptations resulting from imbalanced DA/5-HT signaling in Drosophila mutants lacking neural DA. We find that, similar to rodent models of PD, lack of DA leads to increased 5-HT levels and arborizations in specific brain regions. Conversely, increased DA levels by L-DOPA feeding leads to reduced connectivity of 5-HT neurons to their target neurons in the mushroom body (MB). The observed alterations of 5-HT neuron plasticity indicate that loss of DA signaling is not solely responsible for the behavioral disorders observed in Drosophila models of PD, but rather a combination of the latter with alterations of 5-HT circuitry.